Serum CGRP in migraine patients using erenumab as preventive treatment - de Vries Lentsch, Simone; Garrelds, Ingrid M.; Danser, A. H. Jan; Terwindt, Gisela M.; MaassenVanDenBrink, Antoinette (Journal of headache and pain, 2022)
Aim Serum levels of Calcitonin Gene-Related Peptide (CGRP)-like immunoreactivity (CGRP-LI) in migraine patients before and after starting treatment with erenumab were measured to evaluate the association with clinical treatment response. Methods Blood samples were collected from the cubital fossa before (T0) and 2–4 weeks after (T1) starting treatment with erenumab. Clinical response was monitored using a daily headache e-diary. Serum levels of CGRP-LI, assessed using radioimmunoassay, were compared between T0 and T1, correcting for migraine reduction. In addition, for both T0 and T1, linear regression models were constructed using migraine reduction as outcome and serum CGRP-LI as independent variable, corrected for age, gender and monthly migraine days (MMD) at baseline. Results Serum CGRP-LI did not differ between T0 and T1 ( p = 0.30). However, there was an interaction between time and reduction in MMD ( p = 0.01). Absolute reduction in MMD in the third month after treatment with erenumab was associated with serum CGRP-LI at T1, 2–4 weeks after starting treatment with erenumab ( p = 0.003), but not with serum CGRP-LI at T0 ( p = 0.24). Conclusion Lower serum CGRP-LI 2–4 weeks after starting treatment with erenumab was associated with a higher reduction in migraine days after three months of treatment. Although the underlying mechanisms remain to be determined, this suggests that changes in CGRP levels, shortly after starting erenumab, are important for its clinical effect. Highlights • Lower serum levels of calcitonin gene-related peptide (CGRP)-like immunoreactivity (CGRP-LI) in migraine patients at 2–4 weeks after starting treatment with erenumab were associated with better treatment response after three months. • Early changes in serum CGRP may be important for the clinical effect of erenumab in migraine.